Visible light photocatalysis of fullerol-complexed TiO2 enhanced by Nb doping - Lim, Jonghun; Monllor-Satoca, Damian; Jang, Jum Suk; Lee, Seockheon; Choi, Wonyong (ELSEVIER, 2014)
Visible light photocatalysis by TiO2 nanoparticles modified with both fullerol complexation and Nb-doping (fullerol/Nb-TiO2) demonstrated an enhanced performance. Nb-doped TiO2 (Nb-TiO2) was firstly prepared by a conventional sol-gel method, and subsequently fullerol was adsorbed on the surface of Nb-TiO2. The physicochemical and optical properties of as-prepared fullerol/Nb-TiO2 were analyzed by various spectroscopic methods (TEM, EELS, XPS, and DRS). The adsorption of fullerol on Nb-TiO2 surface increased the visible light absorption through a surface-complex charge-transfer (SCCT) mechanism. Nb-doping enhanced the charge transport and induced the Ti cation vacancies that retarded the recombination of photo-generated charge pairs by trapping the electrons injected from the HOMO level of fullerol. Due to the advantage of simultaneous modification of fullerol and Nb-doping, the visible light photoactivity of fullerol/Nb-TiO2 was more enhanced than either Nb-TiO2 or fullerol/TiO2. The photocatalytic activities of fullerol/Nb-TiO2 for the reduction of chromate (Cr-VI), the oxidation of iodide, and the degradation of 4-chlorophenol were all higher than bare TiO2 and singly modified TiO2 (i.e., Nb-TiO2 and fullerol/TiO2) under visible light (lambda>420 nm). A similar result was also confirmed for their photoelectrochemical behavior: the electrode made of fullerol/Nb-TiO2 exhibited an enhanced photocurrent under visible light. On the other hand, the decay of open-circuit potential of the fullerol/Nb-TiO2 electrode after turning off the visible light was markedly slower than either that of Nb-TiO2 or fullerol/TiO2, which implies the retarded recombination of photo-generated charge pairs on fullerol/Nb-TiO2. In addition, the electrochemical impedance spectroscopic (EIS) data supported that the charge transfer resistance is lower with the fullerol/Nb-TiO2 than either Nb-TiO2 or fullerol/TiO2. This specific combination of the bulk (Nb-doping) and surface (fullerol complexation) modifications of titanium dioxide might be extended to other cases of bulk+surface combined modifications. (c) 2014 Elsevier B.V. All rights reserved.
Keywords: DYE-SENSITIZED TIO2; ANATASE TIO2; SOLAR-CELLS; HYDROGEN; METAL; NANOPARTICLES; POLLUTANTS; ELECTRODES; CONVERSION; INSIGHTS